Optimizing Digital Learning: Navigating Educational Changes in the Era of Rapid Technological Advancement - Mohammad Ahmad Bani Amer; Markhabat Bolat (International Journal of Education and Digital Learning (IJEDL), 2025)
In recent years, digital learning has emerged as a transformative force in the education sector, driven by rapid technological advancements. This study explores the evolution and optimization of digital learning, emphasizing the integration of emerging technologies such as artificial intelligence (AI), virtual reality (VR), and gamification. These innovations have the potential to enhance learning experiences, providing personalized, immersive, and interactive educational environments. However, challenges such as the digital divide, limited access to technology, and the need for teacher preparedness must be addressed to fully optimize the benefits of digital learning. Through a comprehensive review of existing literature and case studies, this article identifies key trends and challenges in the adoption of digital learning tools. It offers practical recommendations for educators and policymakers to ensure equitable access to digital resources, improve teacher training, and integrate emerging technologies effectively into educational practices. Ultimately, the goal is to create an inclusive, engaging, and high-quality learning experience that can cater to diverse learners in the digital age.